Prospects of the Use of Struvite in Soilless Crop Production Systems: a Review - Neofytou, Giannis; Chrysargyris, Antonios; Tzortzakis, Nikos G. (My University, 2025)
The increasing demand for phosphorus (P) and nitrogen fertilizers, driven primarily by the need to meet the increasing food production requirements, has prompted the search for sustainable alternatives. Soilless culture systems, which encompass a range of efficient and intensive crop production methods, mainly rely on the use of synthetic soluble fertilizers to provide the essential nutrients to plants. However, the production and use of these fertilizers is associated with an increased environmental impact. The implementation of recovered materials as alternative fertilizers in these systems has a potential to mitigate these impacts, while simultaneously leveraging the advantages of soilless cultivation. The present work assessed the use of struvite, a byproduct of wastewater treatment, a potential substitute for mineral P fertilizers in soilless cultivation, as outlined in the available literature. The characteristics of struvite complicate its introduction in soilless cultivation, and thus various studies have examined the application of struvite to cover crop needs directly in granules, or via the nutrient solution, with varying degrees of success. Generally, struvite exhibited similar efficacy to conventional fertilization. Furthermore, the struvite dose applied was related to its performance, especially when applied in granular form directly in the growing media. However, the diverse quality and composition of struvite materials used, and the varying synthetic commercial fertilizer quantities employed make it challenging to draw definitive conclusions from existing literature. Additionally, current research lacks a comprehensive understanding of the optimal method of struvite application, while the economic feasibility of struvite, compared to conventional fertilization, requires further investigation.
Keywords: Phosphorus; Struvite; Nutrient recovery; Hydroponics